ETHNOARCHAEOLOGY IN A TRADITIONAL NEIGHBORHOOD OF AYACUCHO, BASED IN ARCHAEOLOGICAL MONITORING - Pérez Calderón, Ismael (2013)
We present archaeological, ethnohistorical and ethnographic to know and understand the cultural roots of the Santa Ana in Ayacucho, established in an area with human occupation since at least the Formative period, according to material culture evidence recorded in the nearby settlements of Pilacucho, Andamarca Waychaupampa and in the neighborhood of Santa Ana, whose square drawn in the colonial era is on the cultural vestiges Huarpa and Wari, during this last period the inhabitants were devoted to the production of pottery, something similar to what was happening in villages and Acuchimay Conchopata. Reference is made of clay outcrops and around the square which had to be used as quarries, presence of human burials in tombs with stone walls and simple pits dug into sterile soil as part of a funeral industry, and remains a midden with abundant ceramic with a high proportion Wari dispersed in the basement of the northeast corner of said open space.